Silicon kerf loss as a potential anode material for lithium-ion batteries - Søiland, Anne-Karin; de Meatza, Iratxe; Muguruza, Ane; Xu, Yijiang; Bellmann, Martin (Frontiers in Photonics, 2024)
In this work industrially processed silicon kerf-loss (abbreviated to silicon kerf) from the photovoltaic industry is assessed as anode material for the lithium-ion battery (LIB). The study includes both characterization of processed silicon kerf from different sources and a comparison with commercially available nanosized silicon (40 and 100 nm) in electrochemical testing. Such a direct comparison between these two silicon types in electrochemical testing provides new insight to silicon kerf as anode material. The silicon kerf particles are flake-like with varying length, with aa mean particle size (d50) d50 measured to ~ 700 nm and one dimension of a few tens' nanometers thickness. HoweverStill, the specific surface area ranging from 20 to 26 m 2 /g is more comparable to that of a silicon material of size a ~100 nm .sized silicon material. The silicon oxide layer surrounding the particles was measured to 1-2 nm in thickness and therefore in suitable range for LIB. In terms of electrochemical performance, the silicon kerf is on par with the commercial nanosized silicon, further emphasizing the supporting the size evaluation frombased on the specific surface area considerations. Initial discharge capacities in the range 700-750 mAh/g-Si/Gr (close to theoretical for the 12 wt% Si mixture with graphite) and first cycle efficiencies of 86-92% are obtained. The cycling stability is comparable between the two materials although the Differential Voltage Analysis (DVA) of the galvanostatic data reveals that only the silicon kerf samples maintain a silicon activity beyond 120 cycles. This study shows that industrially processed silicon kerf has characteristics with similarities to nanosized silicon without downsizing reducing the size of the silicon kerf particles themselves. Considering the low carbon footprint and potentially lower cost, it can thus be an attractive alternative to nano-sized silicon as anode material for the LIB industry.